Current practicality of nanotechnology in dentistry. Part 1: Focus on nanocomposite restoratives and biomimetics - Scott A Saunders (Dove Medical Press, 2009)
Scott A SaundersMirrorMonitor Creativity, Royersford, PA USAAbstract: First described in 1959 by physicist Richard P Feynman, who saw it as an unavoidable development in the progress of science, nanotechnology has been part of mainstream scientific theory with potential medical and dental applications since the early 1990s. Nanoparticles, nanospheres, nanorods, nanotubes, nanofibers, dendrimers and other nanostructures have been studied for various applications to biologic tissues and systems. While many layers of nanotechnologic capability have been envisioned for oral health in the last decade (eg, oral hygiene maintenance, local anesthesia, even whole-tooth replacement), few of these applications have been developed. Part 1 of a three-part series reviews the current clinical utility of nanotechnology’s most tangible contribution to dentistry to date: the restoration of tooth structure with nanocomposites. Characterized by filler-particle sizes of ≤100 nm, these materials can offer esthetic and strength advantages over conventional microfilled and hybrid resin-based composite (RBC) systems, primarily in terms of smoothness, polishability and precision of shade characterization, plus flexural strength and microhardness similar to those of the better-performing posterior RBCs. Available comparative data for nanocomposites and organically-modified ceramic (Ormocer®) restoratives are also reviewed. Finally, plausible “next-phase” trends in current nanorestorative research are judiciously examined, including 1) calcium-, phosphate-, and fluoride-ion-releasing nanocomposites for anticaries applications and 2) restorative systems based on biomimetic emulation of the nanomolecular assembly processes inherent in dental enamel formation using nanorods, nanospheres, and recombinant amelogenins.Keywords: nanostructure, dental restorative, resin-based composite, biomimetic, amelogenin